2005
DOI: 10.1242/dev.01806
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic zebrafish reveal stage-specific roles for Bmp signaling in ventral and posterior mesoderm development

Abstract: ventral and posterior mesoderm during trunk and tail outgrowth, we generated a transgenic zebrafish line containing a heatshock-inducible dominant-negative Bmp receptor-GFP fusion. Our data show that Bmps are important for tail organizer formation and for patterning the ventral mesoderm during early gastrulation. However, from mid-gastrulation to the early somitogenesis stages, Bmp signaling is important for ventral tail fin development and for preventing secondary tail formation. We conclude that the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
196
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(216 citation statements)
references
References 52 publications
19
196
1
Order By: Relevance
“…The mutant lines used were: Tg(hsp70l:dnXla.Bmpr1a-GFP) (Pyati et al, 2005) and Tg(BRE:mRFP) (Wu et al, 2011). Morpholinos (Gene Tools) were injected as described (Wu et al, 2011) at the indicated doses and are listed in supplementary material Table S1.…”
Section: Fish Maintenance and Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutant lines used were: Tg(hsp70l:dnXla.Bmpr1a-GFP) (Pyati et al, 2005) and Tg(BRE:mRFP) (Wu et al, 2011). Morpholinos (Gene Tools) were injected as described (Wu et al, 2011) at the indicated doses and are listed in supplementary material Table S1.…”
Section: Fish Maintenance and Strainsmentioning
confidence: 99%
“…1A, right panel). We next determined exactly when BMP signalling is required for NC development using a transgenic zebrafish line expressing a dominant-negative BMP type I receptor (dnBMPR1a) in response to heat shock [Tg(hsp70l:dnXla.Bmpr1a-GFP)] (Pyati et al, 2005). This line enabled us to perturb BMP activity at specific stages.…”
Section: Research Articlementioning
confidence: 99%
“…Heat-shock-inducible transgenic approaches have provided an invaluable tool through which gene expression in development can be modulated (Halloran et al, 2000;Xiao et al, 2003;Burns et al, 2005;Pyati et al, 2005). To establish if co-injection techniques along with heat-shock-inducible transgenesis could be used to elicite gene expression within established tumors, the rag2-kRASG12D, rag2-GFP and hsp70-dsRED2 constructs were co-injected into one-cell stage AB-strain animals.…”
mentioning
confidence: 99%
“…This is largely due to the crucial role of Bmp4 at an early stage of gastrulation (Winnier et al, 1995). In zebrafish, constitutive activation of the Bmp receptor Bmpr1b in the tailbud leads to an expansion of the T-positive mesoderm progenitor zone (Row and Kimelman, 2009), while transgenic expression of a dominant-negative version of the same receptor leads to ectopic tail formation (Pyati et al, 2005).…”
Section: Mesoderm Progenitor Maintenancementioning
confidence: 99%
“…In frog and chick embryos, both gain-and loss-offunction studies identified a role for Bmp4 and Bmpr1 in tailbud outgrowth and somite differentiation (Beck et al, 2001;Reshef et al, 1998;Row and Kimelman, 2009). In zebrafish, loss of Bmp results in ventral fin and tail mesoderm defects (Pyati et al, 2005;Stickney et al, 2007). However, similar comprehensive studies on the later role of Bmp signaling in axis elongation and tail somite formation in mice have been hampered by the essential role of Bmp4 during gastrulation (Winnier et al, 1995).…”
Section: Introductionmentioning
confidence: 99%